THU0304 Vasculitis patients admitted to intensive care unit: implications from a single-center retrospective study. (15th June 2017) - Watad, A; Shovman, O; Bragazzi, NL; Shoenfeld, Y; Amital, H; Haviv, Y
Abstract : Background: Vasculitides are a heterogeneous group of disorders that are characterized by the inflammation of the vasculature vessels. Vasculitides may present as a life-threatening condition and cause higher rates of morbidity and mortality. There are few studies assessing the outcome and prognosis of patients with vasculitides admitted to the intensive care (ICU). Objectives: To assess the outcome of vasculitides patients required admission to ICU and to identify factors associated with mortality Methods: A retrospective study was carried out, including all patients who were diagnosed with vasculitides and admitted to the ICU of the Sheba Medical Center, Tel-Hashomer, throughout the years 2000–2014. Continuous variables were computed as mean±standard deviation, whilst categorical variables were recorded as percentages, where appropriate. Student's t-test and chi-squared analyses were performed for investigating the impact of the clinical variables on mortality. Results: Twenty-five vasculitides patients admitted to the ICU were included in the present study (mean age 52±14y, sex ratio M/F: 12/13). The mortality rate among these patients was 48%. Leading causes for ICU admission were: infection (64%), vasculitides exacerbation (34%), and hemorrhage (16%). Variables significantly associated with mortality were: the use of Rituximab prior to admission ICU (p=0.039), involvement of the hemodynamic system (p=0.024), the SOFA score (p=0.041), blood infections during the first week at ICU (p=0.018) and persisting after the first week (p=0.007). Conclusions: Our study confirms the high mortality rate among vasculitides patients and mainly among those requiring admission to ICU. SOFA score and pre-admission treatment with rituximab have been found to be predictive of mortality. Disclosure of Interest: None declared